THESES AND DISSERTATION COMPLETED AT THE CENTER FOR RELIGION STUDIES FROM UFRGS: CURRENT SITUATION AND PRELIMINARY QUANTITATIVE ANALYSIS - Alves, Daniel (Debates do NER, 2007)
This paper exarnin the setting up of the Center for Religion Studies (NER) at the Federal University of Rio Grarde do Sul (UF1S), in Bra2!l. NER is a research group cornposed by scholars and students of religion sociology and anthiopolcgy. It is part of a wider histthcal contsct in which religion is view1 as a social fact to be studd in loco and rnostly analyzed frorn the persctiw of social anthiopolcgy. The establishnunt and consolidalion of NER has enabd its assodate reseacheis to supeivise a nurnbe of these and dissertations and hence contiibut1 to a recert in cr se in the nurnbe of studs on religion